Amphetamine Modulation of Long-Term Object Recognition Memory in Rats: Influence of Stress - Colucci, Paola; Santori, Alessia; Romanelli, Luca; Zwergel, Clemens; Mai, Antonello; Scaccianoce, Sergio; Campolongo, Patrizia (Frontiers in Pharmacology, 2021)
Amphetamine is a potent psychostimulant that increases brain monoamine levels. Extensive evidence demonstrated that norepinephrine is crucially involved in the regulation of memory consolidation for stressful experiences. Here, we investigated amphetamine effects on the consolidation of long-term recognition memory in rats exposed to different intensities of forced swim stress immediately after training. Furthermore, we evaluated whether such effects are dependent on the activation of the peripheral adrenergic system. To this aim, male adult Sprague Dawley rats were subjected to an object recognition task and intraperitoneally administered soon after training with amphetamine (0.5 or 1 mg/kg), or its corresponding vehicle. Rats were thereafter exposed to a mild (1 min, 25 ± 1 °C) or strong (5 min, 19 ± 1 °C) forced swim stress procedure. Recognition memory retention was assessed 24-h after training. Our findings showed that amphetamine enhances the consolidation of memory in rats subjected to mild stress condition, while it impairs long-term memory performance in rats exposed to strong stress. These dichotomic effects is dependent on stress-induced activation of the peripheral adrenergic response.